2015
DOI: 10.1155/2015/756359
|View full text |Cite
|
Sign up to set email alerts
|

A Pyrosequencing Assay for the Quantitative Methylation Analysis ofGALR1in Endometrial Samples: Preliminary Results

Abstract: Endometrial cancer is the most common malignancy of the female genital tract while aberrant DNA methylation seems to play a critical role in endometrial carcinogenesis. Galanin's expression has been involved in many cancers. We developed a new pyrosequencing assay that quantifies DNA methylation of galanin's receptor-1 (GALR1). In this study, the preliminary results indicate that pyrosequencing methylation analysis of GALR1 promoter can be a useful ancillary marker to cytology as the histological status can su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Previous studies have used the t-test or ANOVA 39 41 or the non-parametric Kruskal-Wallis test 42 44 to evaluate the differences of DNA methylation levels in single CpG site or the average of several sites among groups. However, the DNA methylation levels among CpG sites within a gene may be correlated 28 . Our present study also revealed that there were significant correlations among the methylation percentages of 3 CpG sites and the average of 3 CpG sites (p < 0.0001) (Table 3 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have used the t-test or ANOVA 39 41 or the non-parametric Kruskal-Wallis test 42 44 to evaluate the differences of DNA methylation levels in single CpG site or the average of several sites among groups. However, the DNA methylation levels among CpG sites within a gene may be correlated 28 . Our present study also revealed that there were significant correlations among the methylation percentages of 3 CpG sites and the average of 3 CpG sites (p < 0.0001) (Table 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, no study has used pyrosequencing to quantify DNA methylation levels of the DLGAP2 gene; in addition, no study has examined the methylation of DLGAP2 gene in TD. Furthermore, the DNA methylation levels using pyrosequencing among CpG sites within a gene may be correlated 28 . Mixed models (also known as multilevel models or hierarchical models) including both fixed effects and random effects have been developed to deal with correlated data 29 33 .…”
Section: Introductionmentioning
confidence: 99%
“…For this purpose, they combined a high-throughput procedure with a non-invasive collection technique for early diagnosis of endometrial cancer [ 35 , 36 ]. The study by Kottaridi et al has argued that pyrosequencing technology plays an important role as an indicator of malignant tumors [ 37 ]. They analyzed the mean methylation of thirteen CpG sites in the GALR1 promoter in malignant and normal endometrial specimens.…”
Section: Pyrosequencingmentioning
confidence: 99%